THE STATUS AND SOME FACTORS RELATED TO SATISFACTION OF PATIENTS AT YEN PHONG GENERAL CLINIC, BAC NINH PROVINCE, IN 2021 (Vietnam Journal of Community Medicine, 2022)
Background: According to the World Health Organization (WHO), the quality of health services affects patient satisfaction (NB) and conversely, patient satisfaction can be assessed by the effectiveness of services provided by the facilities. Therefore, patient is the direct object of determining the assessment of the reputation and quality of service delivery at the facilities.Objectives: Determining the status and some factors related to patient satisfaction at Yen Phong general clinic, Bac Ninh province.Methods: Cross-sectional survey, quantitative research.Results: This study collected information from 310 patients at 2 departments (Medical examination and hospital pharmacy) of the Yen Phong general clinic, Bac Ninh province through questionnaire interviews. Research results show that 5/5 fields have satisfaction rates of over 82%.Conclusion: The overall satisfaction rate of patients is quite high (82.3%). The average score is 4,17 ± 0,38. The factor related to the satisfaction of patients are sex (p
Keywords: Satisfaction, patient, related factors.